The in Vivo Effects of Extracts of the Anti-Asthmatic Plant, Dbsmodium Adscendens on Anaphylaxis - Awumey, E.M.K (University of Ghana, 1981)
Desmodium adscendens is used as prophylaxis in asthma. Earlier work in this ^laboratory on the scientific basis for the therapeutic action of the plant indicated that both the aqueous and alcoholic extracts were anti-anaphylactic in vitro. Since extracts of the plant are taken orally by asthmatic patients, the present work was carried out to investigate the in vivo effects of both alcoholic and aqueous extracts of D. adscendens on anaphylaxis. The methods used were the contraction of the isolated guinea-pig ileum, the histamine-induced spasm, the release of smooth musclestimulating substances from the guinea-pig lung and the histamine content of such lung tissue. The results show that the extracts of D. adscendens caused a significant reduction in the anaphylactic contraction of the guinea-pig ileum and rendered it less sensitive to histamine when compared with controls. The quantities of mediators of smooth muscle contraction released from the lung tissue of the treated animals were significantly less than those in the untreated animals. Furthermore, the total histamine content of the lung tissue in animals treated with the extracts of D. adscendens was significantly less than that in the untreated animals. The results have provided mSre evidence for the earlier indication of the anti-anaphylactic property of the plant extracts, a property which may underlie their usefulness as antiasthmatic agents in folklore medicine.
Thesis (MSc)-University of Ghana, 1981